Thyroid Disorders and the Level of Malondialdehyde - Ali, Eham A.; Tahseen, Yildiz H.; El-Yassin, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Free radicals have been implicated in many pathological processes, including ischemia, inflammation, and malignancy. The free radicals may affect tissues damage by lipid peroxidation which generate malondialdehyde (MDA) as a by byproduct of the reaction. The objective of this study is to examine the dynamics of lipid peroxidation in patients with thyroid disorders using the measurement of malondialdehyde level as a marker for the degree of thyroid disorder. Methods: Two hundred and forty five subjects were enrolled in this study. Hundred and ninety five were patients with different thyroid disorders (88 yperthyroidism, 63 hypothyroidism and 44 thyroid carcinoma) the remaining 50 subjects were healthy ones without any apparent functional disorders served as a control. Malondialdehyde (MDA) level was estimated in the sera of all subjects. Results: A significant increase in the level of serum MDA concentration was observed in patients with all types of thyroid disorders as compared with the control groups. Conclusion: The findings obtained showed a high rate of lipid peroxidation.